Determining The Location of an Impact Site from Bloodstain Spatter Patterns: Computer-Based Analysis of Estimate Uncertainty. - March, Jack (2005)
The estimation of the location in which an impact event took place from its resultant impact spatter bloodstain pattern can be a significant investigative issue in the reconstruction of a crime scene. The bloodstain pattern analysis methods through which an estimate is constructed utilise the established bloodstain pattern analysis principles of spatter bloodstain directionality, impact angle calculation, and straight-line trajectory approximation.